PERSUASIVE STRATEGIES USED IN BURGER KING’S INSTAGRAM POSTS CAPTION - Rudito, Yeremia Yori; Anita, Anita (Journal of Language and Literature, 2020)
Burger King is the one of the most successful fast food restaurant in the world. According to Wikipedia, there are 17,796 locations of Burger King all over the world in 2018. Burger King also has its Instagram account. Now this account has been followed by 1,6 million people and has posted 938 posts. That statistic shows that Burger King is active in social media especially in Instagram platform. The writer see the indication of the using of Persuasive Strategies because in promoting their product. In this research the writer wants to know the persuasive strategies that applied in Burger King’s Instagram post caption and the most used strategy. This research applied Qualitative Method as research method. This research has two findings, first, there are 13 strategies that appear in Burger King’s Instagram post caption they are, Anecdote, Assonance, Cliché, Connotation, Evidence, Everyday/Colloquial Language, Hyperbole, Imagery, Inclusive Language, Pun, Repetition, Rhetorical Question, and Simile. Second, the most used strategy is Everyday/Colloquial Language.